Studies on Hypoxanthine-Guanine Phosphoribosyltransferase in Fibroblasts from Patients with the Lesch-Nyhan Syndrome - William N. Kelley; Jean C. Meade (1971)
Abstract The Lesch-Nyhan syndrome has been characterized by an apparently complete deficiency in erythrocytes of an enzyme of purine metabolism, hypoxanthine-guanine phosphoribosyl-transferase. Recent studies have suggested that low levels of this enzyme may be present in skin fibroblasts cultured from these patients. In the present study, we have confirmed the presence of hypoxanthine-guanine phosphoribosyltransferase in these mutant cells. The mean activity in 11 mutant strains ranged from 0.6 to 7% of that observed in normal cells. This low level of activity did not appear to be due to the presence of another enzyme or enzymes with similar activity or to contamination of the cultured cells. Hypoxanthine-guanine phosphoribosyltransferase from nine mutant strains was found to exhibit certain distinctive properties. In contrast to the normal enzyme, the enzymes from eight mutant strains were relatively heat-labile and the enzyme from one mutant strain was not responsive to product inhibition by GMP or IMP. These findings provide evidence for substantial heterogeneity of the mutations leading to a deficiency of hypoxanthine-guanine phosphoribosyltransferase in the Lesch-Nyhan syndrome. In addition, the finding of functionally altered enzyme in at least 10 of the mutant strains provides evidence that in these cases the genetic alteration responsible for the deficiency of hypoxanthine-guanine phosphoribosyltransferase resides in a structural gene coding for the enzyme.